2007
DOI: 10.2174/138955707780363846
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Medicinal Chemistry

Abstract: Microwave irradiation has been used to enhance organic reactions since the mid 80's, its use within the field of medicinal chemistry is not so widely evident in the literature. The present review highlights the use of microwave chemistry as an important tool for the fast development of structure activity relationship in several programs related to various therapeutic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Considering the fast reaction onset provided by microwaves of only a few seconds, and the ratio between the volume of the NMR chip and the microwave cell, which allows the latter to be divided into different zones for analysis, several data An important discipline where microwave irradiation has already had a major impact is medicinal chemistry [25][26][27][28][29][30]. Microwave-assisted continuous flow organic synthesis (MACOS) has also been used in this field.…”
Section: Microfluidic Reactorsmentioning
confidence: 99%
“…Considering the fast reaction onset provided by microwaves of only a few seconds, and the ratio between the volume of the NMR chip and the microwave cell, which allows the latter to be divided into different zones for analysis, several data An important discipline where microwave irradiation has already had a major impact is medicinal chemistry [25][26][27][28][29][30]. Microwave-assisted continuous flow organic synthesis (MACOS) has also been used in this field.…”
Section: Microfluidic Reactorsmentioning
confidence: 99%
“…The microwave irradiation method has been exploited for many chemical reactions. A number of review papers on microwave‐assisted chemical reactions have been published . This method allows rapid and direct heating of the reaction media.…”
Section: Introductionmentioning
confidence: 99%
“…A number of review papers on microwave-assisted chemical reactions have been published. [16][17][18][19] This method allows rapid and direct heating of the reaction media. In most cases, microwave can dramatically reduce reaction times and increase product yields.…”
mentioning
confidence: 99%
“…It was found that microwave irradiation and solid support in solventless conditions considerably shortens reaction time and greatly reduces waste production. [16][17][18] In this paper we report the synthesis in good yield of a variety of β-aminoketones of potential biological interest under environmentally friendly conditions, using microwave-supported Michael-addition. This protocol includes reactions that can be conducted without solvent and in absence of metal catalysts, a highly desirable experimental condition.…”
Section: Introductionmentioning
confidence: 99%